2018
DOI: 10.1038/s41467-018-05723-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and scalable synthesis of highly aligned and compact two-dimensional nanosheet films with record performances

Abstract: It is crucial to align two-dimensional nanosheets to form a highly compact layered structure for many applications, such as electronics, optoelectronics, thermal management, energy storage, separation membranes, and composites. Here we show that continuous centrifugal casting is a universal, scalable and efficient method to produce highly aligned and compact two-dimensional nanosheets films with record performances. The synthesis  mechanism, structure  control and property  dependence of alignment and compacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
143
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(149 citation statements)
references
References 66 publications
0
143
0
Order By: Relevance
“…In our previous study, we reported a continuous centrifugal casting (CCC) method to synthesize highly aligned and compact two‐dimensional (2D) nanosheets films. [ 35 ] In the CCC method, the dispersion of 2D nanosheets is continuously cast/sprayed onto the inner surface of a rotating hollow tube (RHT) accompanied with low temperature heating. The alignment of 2D nanosheets is achieved by a shear force along the tangential direction of RHT, which is generated by the velocity difference between the tube and liquid, while the compaction is realized by a centrifugal force along the radial direction of the tube that is generated by high speed rotating.…”
Section: Figurementioning
confidence: 99%
“…In our previous study, we reported a continuous centrifugal casting (CCC) method to synthesize highly aligned and compact two‐dimensional (2D) nanosheets films. [ 35 ] In the CCC method, the dispersion of 2D nanosheets is continuously cast/sprayed onto the inner surface of a rotating hollow tube (RHT) accompanied with low temperature heating. The alignment of 2D nanosheets is achieved by a shear force along the tangential direction of RHT, which is generated by the velocity difference between the tube and liquid, while the compaction is realized by a centrifugal force along the radial direction of the tube that is generated by high speed rotating.…”
Section: Figurementioning
confidence: 99%
“…Our theoretical analysis shows the importance of 2D nature of the metallic material for achieving multiple reflections and strong attenuation of electromagnetic waves. Also, considering that the conductivity of micron‐thick films of Ti 3 C 2 T x already exceeds 10 000 S cm −1 and further improvements are expected, more than 30 MXenes are already available and dozens more underway, there are exciting opportunities for further control of microwaves with ultrathin films of metallic 2D carbides and nitrides produced by scalable solution processing …”
mentioning
confidence: 99%
“…Concurrently, along with the increase of the contents of MTM nanosheets, the full width at the half maximum (FWHM) of dominant XRD peaks becomes smaller (Figure a,b). Similar results have been observed before in clay nanocomposites, indicating the better in‐plane alignment of 2D nanosheets . It is likely the presence of larger amounts of MTM nanosheets in the top layer poses additional spatial restriction for ordering so that the statistical distribution of in‐plane orientation is reduced (Figure c) as supported by simulations .…”
Section: Resultsmentioning
confidence: 99%